2021
DOI: 10.1038/s41598-021-99621-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of organic cation orientation in formamidine based perovskite materials

Abstract: The rotation of organic cations is considered to be an important reason for the dynamic changes in stability and photoelectric properties of organic perovskites. However, the specific effect of organic cations rotation on formamidine based perovskite is still unknown. In our work, first-principles calculations based on density functional theory are used to examine the effect of the rotation of formamidine cations in FAPbI3 and FA0.875Cs0.125PbI3. We have comprehensively calculated the structure, electronic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 46 publications
(55 reference statements)
0
16
0
Order By: Relevance
“…Figure 3a depicts the amplitude spectrum of the emitted field, the ~0.4 THz peak increased steeply with the photon energy change from 2.38 eV to 2.43 eV, and the amplitude of the ~0.4 THz peak in 0.95FA surpasses that of the ~1 THz peak when the pump photon energy is higher than 2.4 eV. It has been reported that FA cation rotational phonon mode is in the frequency of ~0.3–0.5 THz 31 , 32 and the FA cation energy level is involved only in the higher sub-conduction band in HOIP 40 42 . Therefore, it is reasonable to assign the enhanced part of THz emission at P2 to the collision between rotated FA cation and the hot electrons with increased density in the FA energy level.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Figure 3a depicts the amplitude spectrum of the emitted field, the ~0.4 THz peak increased steeply with the photon energy change from 2.38 eV to 2.43 eV, and the amplitude of the ~0.4 THz peak in 0.95FA surpasses that of the ~1 THz peak when the pump photon energy is higher than 2.4 eV. It has been reported that FA cation rotational phonon mode is in the frequency of ~0.3–0.5 THz 31 , 32 and the FA cation energy level is involved only in the higher sub-conduction band in HOIP 40 42 . Therefore, it is reasonable to assign the enhanced part of THz emission at P2 to the collision between rotated FA cation and the hot electrons with increased density in the FA energy level.…”
Section: Resultsmentioning
confidence: 97%
“…The hot carriers with excess energy in HOIPs were generally considered to be coupled to inorganic sublattice vibration (~1 THz) after fast relaxation to the bottom of conduction band 9 , 39 . Meanwhile, it has been reported theoretically that there are two different conduction bands (CB1 and CB2) existing in FAPbI 3 , and the energy gap from the top of the valence band to FA cation level is about 2.4eV 40 42 . Therefore, it is reasonable to speculate whether the hot electron could couple with the A-site cation rotation (~0.4 THz).…”
Section: Resultsmentioning
confidence: 99%
“…to the coupling effect between the orientation of organic cations and the addition of cesium. 155 The electronic properties of FAPbI 3 and the most probable orientation of the FA cation are explored in the combination of first-principles calculations and experimental study by Sun et al 43 They provided temperature and pressure impact on the FAPbI 3 bandgap. As expected, temperature decrease from T = 300 K to T = 250 K reduces lattice parameters and Pb I bond lengths and results in bandgap degradation of about 0.017 eV.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, they stated that the variation of the absorption spectrum with X could be characterized by the wellknown sum rule (Figure 8D). In a theoretical study, Liu et al 155 revealed that the substitution of Cs + and the rotation of FA + in different orientations change the optical properties of FA-based perovskites. They showed that introducing Cs contracts the value of the static dielectric constant in FA 0.875 Cs 0.125 PbI 3 .…”
Section: Atomic Substitution Role In the Optical Enhancementmentioning
confidence: 99%
See 1 more Smart Citation